The Contribution of Cultural Harmony in Enhancing Local Wisdom in Tiuh Tohou Village, Tulang Bawang - Miftahuddin; Ehwanudin; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to analyze the contribution of cultural harmony in strengthening local wisdom within the community of Tiuh Tohou Village, Tulang Bawang Regency. This research employs a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that cultural harmony plays a significant role in preserving and reinforcing local wisdom, which is reflected in social interactions based on tolerance, mutual cooperation, deliberation, and mutual respect. These values contribute to strengthening social solidarity and community integration, as well as serving as an effective medium for transmitting cultural values to younger generations. This process is supported by the active role of traditional leaders and the collective awareness of the community. However, globalization and technological development present challenges by encouraging individualistic lifestyles and reducing youth participation in traditional cultural activities. Therefore, cultural harmony functions not only as a mechanism of social cohesion but also as an adaptive filter that enables local wisdom to remain relevant amid the dynamics of modernization.